2014
DOI: 10.3109/03014460.2014.932008
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous populations in transition: An evaluation of metabolic syndrome and its associated factors among the Toba of northern Argentina

Abstract: Background The health problems associated with rapidly changing lifestyles in indigenous populations, e.g., cardiovascular disease, are becoming a public health concern. Aim The objective of this study was to evaluate the prevalence of metabolic syndrome and analyze the metabolic conditions that define this syndrome, in an indigenous Toba community of northern Argentina. Subjects and Methods A total of 275 adults participated in this study. Anthropometric (BMI, body fat percentage, waist circumference) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Sustained physical activity levels and persistent reliance on low‐fat, less calorically dense, subsistence‐based foods may help explain why Tsimane’ prevalence of obesity remained below those reported for other indigenous populations in lowland South America around the same time period, including Toba women and men (~ 45%) of Argentina in 2010 , Wichí women and men (~ 15%) of Argentina in 2005 , Mbyá women and men (~ 15%) of Argentina in 2003 , and Suruí women (~ 25%) and men (~ 12%) of Brazil in 2005 . A shift from reliance on slash‐and‐burn agriculture, hunting, fishing, and foraging to more market‐purchased foods, such as refined flour, pasta, oil, and fatty meats, have been noted in studies of other South American indigenous populations .…”
Section: Discussionmentioning
confidence: 98%
“…Sustained physical activity levels and persistent reliance on low‐fat, less calorically dense, subsistence‐based foods may help explain why Tsimane’ prevalence of obesity remained below those reported for other indigenous populations in lowland South America around the same time period, including Toba women and men (~ 45%) of Argentina in 2010 , Wichí women and men (~ 15%) of Argentina in 2005 , Mbyá women and men (~ 15%) of Argentina in 2003 , and Suruí women (~ 25%) and men (~ 12%) of Brazil in 2005 . A shift from reliance on slash‐and‐burn agriculture, hunting, fishing, and foraging to more market‐purchased foods, such as refined flour, pasta, oil, and fatty meats, have been noted in studies of other South American indigenous populations .…”
Section: Discussionmentioning
confidence: 98%
“…Unlike non-Native Argentines, the Qom show a positive association between socioeconomic status and BMI (Valeggia et al, 2010), which has been observed in other Argentinean indigenous groups (Orden and Oyhenart, 2006;Romaguera et al, 2008) for whom heavy individuals are regarded as "healthy" (Valeggia et al, 2010). Moreover, a previous study has shown that Westernized Qom adults show a prevalence of obesity that is above 45% (Lagranja et al, 2015). It is important to note, however, that Qom WAZ scores are very close to the Argentine median (Lejarraga et al, 2009), which, when contrasted with the high BMIZ scores of these children, indicate that the Argentine reference for weight is skewed toward the right, further highlighting the importance of applying international standards (de Onis and Lobstein, 2010).…”
Section: Discussionmentioning
confidence: 77%
“…Changes in diet associated with urbanization have been reported in other studies, where geographic location plays an important role (Lazarou and Kalavana, 2009). Moreover, a previous study has shown that Westernized Qom adults show a prevalence of obesity that is above 45% (Lagranja et al, 2015). Unlike non-Native Argentines, the Qom show a positive association between socioeconomic status and BMI (Valeggia et al, 2010), which has been observed in other Argentinean indigenous groups (Orden and Oyhenart, 2006;Romaguera et al, 2008) for whom heavy individuals are regarded as "healthy" (Valeggia et al, 2010).…”
Section: Discussionmentioning
confidence: 81%
“…Most studies of Indigenous people in South America reveal a relatively high prevalence of low HDL-C and increased WC for women [24,[27][28][29]. High obesity (BMI>30) prevalences were particularly more frequently observed in Indigenous populations with an acculturated sedentary life style [9,30,31]. A study among the Xavante living in a reservation in Brazil revealed a high prevalence of MeTS of 66% [9].…”
Section: Discussionmentioning
confidence: 99%